Analisis Perencanaan Pembangunan Jaringan Fiber Optik pada Pemerintahan Kota Palembang - Muhammad Ibrahim; Suryayusra; Alex Wijaya (Sci-tech Journal, 2024)
To communicate and share data, the Palembang city government's regional apparatus work unit (SKPD) office requires an immediate internet connection. The SKPD office is still using various internet service providers (ISPs) at this time, so any network issues won't be fixed immediately by the previous ISP. To resolve this issue, a separate network infrastructure centered in the Palembang mayor's office is required. The Palembang city government will be able to control the network because the SKPD offices will be able to communicate with one another and share data as a result of this.. The organization foundation that will be utilized is fiber optics, since fiber optics have a high web access speed, and have a steady sign so information move will be quicker, more successful and furthermore productive. This study employs the NDLC method, which is a method for building a computer network